Characterization and phylogenetic analysis of the complete mitochondrial genome of Glossogobius giuris (Perciformes: Gobiidae) - Pengfei Wang; Chao Zhao; Sigang Fan; LuLu Yan; Lihua Qiu (Mitochondrial DNA. Part B. Resources, 2018)
The species tank goby (Glossogobius giuris) is assessed as Least Concern on the IUCN Red List of Threatened Species. In the present study, we first determined and described the complete mitochondrial genome of G. giuris. The circular genome is 16,595 bp in length. It has the typical vertebrate mitochondrial gene arrangement and consists of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and one non-coding control region. The overall base composition is 29.1% for A, 24.6% for T, 29.4% for C, and 17.0% for G. Phylogenetic analysis of 21 species in the family Gobiidae showed that G. giuris was clustered into the genus Glossogobius, subfamily Gobiinae. This information will contribute to future phylogenetic studies of Gobiidae and conservation strategies for G. giuris.